Specific characteristics of micro sheet metal working - Eckstein, Ralf; Geiger, Manfred; Engel, Ulf (SHEET METAL 1999, Proc. Of the Int. Conf. SheMet‘99, 27-28 Sep 1999, Erlangen, Germany, 1999)
None
LFT Import::2019-08-05 (1999)